2002
DOI: 10.1159/000056284
|View full text |Cite
|
Sign up to set email alerts
|

Low Psychopathology Scores in the Prognosis of Breast Cancer

Abstract: Background: Research findings regarding the influence of psychopathology on cancer progression are not yet clear. This preliminary report investigates the severity of psychopathology assessed before biopsy in patients with invasive breast carcinoma (IBC) and its association with two follow-up outcomes: disease-free (to first recurrence) and survival periods. Method: The psychiatric assessment of 80 patients under 70 years old was established by means of an interview before biopsy. The DSM-IV criteria were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Even though at this point the design of therapeutic non-pharmacological protocols specifically aimed at improving the QoL of CHF patients might seem reasonable [21, 22], before resources are invested in any intervention of this sort, its effectiveness and cost-effectiveness must first be prospectively evaluated [23]. Further studies using more precise psychometric instruments than MLHFQ [24, 25]may help to better clarify the role of psychological interventions [26].…”
Section: Discussionmentioning
confidence: 99%
“…Even though at this point the design of therapeutic non-pharmacological protocols specifically aimed at improving the QoL of CHF patients might seem reasonable [21, 22], before resources are invested in any intervention of this sort, its effectiveness and cost-effectiveness must first be prospectively evaluated [23]. Further studies using more precise psychometric instruments than MLHFQ [24, 25]may help to better clarify the role of psychological interventions [26].…”
Section: Discussionmentioning
confidence: 99%
“…Garssen, upon summarizing ~30 years of research, identified stressful life events, social relationships, distress levels and the number of psychological problems, having a psychiatric diagnosis, repression, coping style, and personality factors, loss events, and locus of control, as potential factors (15). Some studies have further demonstrated that psychosocial factors are associated with the occurrence of cancer (16,17), while other studies considered them to be associated with cancer prognosis (18,19), and even recurrence and metastasis (20,21). To further advance our understanding of this association, we investigated the impact of life events and social support on the occurrence of laryngeal cancer and observed that the two groups exhibited significant differences in terms of scores on the life events and social support scales, and on all dimensions of the EPQ (P<0.05), except the psychoticism scale.…”
Section: Discussionmentioning
confidence: 99%
“…Leigh et al (1987) found that depression, trait anxiety and state anxiety predicted longer survival among cancer patients undergoing radiation. Trikas et al (2002) found that a high pre-biopsy psychopathology score predicted less recurrence and longer survival among breast cancer patients. Brown et al (2000) found that negative mood predicted longer survival among early stage melanoma patients.…”
Section: Depressionmentioning
confidence: 99%